Practical Aspects of Interface Application in CPAP Treatment - Adel Bachour; Heidi Avellan-Hietanen; Tuula Palotie; Paula Virkkula (Canadian Respiratory Journal)
While continuous positive airway pressure (CPAP) is an effective first-line therapy for sleep apnea, CPAP fails in one third of patients mainly due to poor adherence to the CPAP device and masks. The role of the medical team is to guide the patient in choosing the best mask, thus insuring good CPAP therapy adherence. Once a suitable mask is found, the brand of the mask does not affect patient satisfaction or CPAP adherence. For the majority of patients, nasal masks are by far more suitable than oronasal masks. Orosanal masks are indicated in case of nasal stuffiness or when an air leak manifests through the mouth. Re-evaluation of the efficacy of CPAP therapy is recommended when switching to oronasal masks.